The Stylistic Functions of Number Forms of Collective Nouns in Lithuanian and English - Браженене, Нийоле (Kalbotyra, 1987)
The contrastive analysis of collective nouns in Lithuanian and English has shown differences and similarities both on morphological and syntactic levels. Apart from their denotative meaning, collectives may have various connotative functions in both languages. The variability of number forms of the collective nouns discloses different stylistic functions: intensity, hyperbolization, frequency, reiteration. The most expressive use of collectives is found in belles-lettres and spoken language.